The impact of relational factors on sexual satisfaction among heterosexual and homosexual men - Carvalheira, Ana (2015)
This study analyzed the correlates of sexual satisfaction among exclusively heterosexual and homosexual men. Analyses were carried out using data from a 2011 web survey about male sexual interest in two European countries. A total of 2968 men with exclusive heterosexual behavior and 285 men with exclusive homosexual behavior in the previous five years from Portugal and Croatia, participated in this study. Hierarchical multiple regressions were performed in order to explore which variables predicted sexual satisfaction. Among heterosexuals, in step one, both age and sexual difficulties emerged as highly significant predictors, and in step two, the frequency of intercourse and the number of sexual partners also emerged as significant predictors. Finally, in the third step, the intimacy and the length of the relationship emerged as highly significant predictors of sexual satisfaction. Among homosexuals, in step one, sexual difficulties and country were significant predictors, in step two, only the frequency of sexual intercourse was a significant predictor, and in step three, both relational variables (relationship length and relationship intimacy) were significant predictors. The findings suggest that relational factors, particularly couple intimacy were the strongest predictors of sexual satisfaction for both heterosexual and homosexual men.